Legal Analysis of Cancellation of Deed of Granting Mortgage Rights (APHT) Which Has The Potential to Be Defamatory to Creditors (Study of Semarang District Court Decision Number 11/Pdt.G/2023/PN Smg Jo. 405/PDT/2023/PT SMG ) - Pambudi, Laksana Yudha Putra (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The bank as a creditor and holder of the mortgage rights is still under threat when there is a judge's decision that cancels the mortgage rights. The objectives of the study are 1) To analyze the judge's decision in case number 11/Pdt.G/2023/PN SMG Jo. 405/PDT/2023/PT SMG; 2) To analyze the legal consequences that occur in the event of cancellation of APHT; 3) To analyze the legal protection for the banking party as a creditor for the cancellation of APHT. This research method is normative legal research with a legislative approach and a case approach. The data used is secondary data. Data collection uses literature studies and data analysis uses qualitative analysis methods. The results of the study are 1) the decision of the panel of judges in case 11/Pdt.G/2023/PN SMG if based on laws and regulations is appropriate and this is reinforced by decision number 405/PDT/2023/PT SMG but if associated with field facts and the principle of legal certainty, the decision to cancel and delete APHT-SHT is not in accordance with the principle of legal certainty. 2) The legal consequences of the cancellation of APHT are the loss of guarantees of debt receivables for creditors along with the privileges attached because the creditor's position is a concurrent creditor. 3) legal protection that can be received by creditors is in the form of the formation of laws and regulations that protect creditors' rights in the event of cancellation of APHT as preventive legal protection while repressive legal protection is litigation and non-litigation legal efforts that can be carried out by creditors.